RIBA (USURY); A TOOL THAT SHOULD BE CARVED OUT OF FINANCIAL TRANSACTIONS - Ibrahim Mohammad LAWAL (Türkiye İslam İktisadı Dergisi)
Riba has been major driving force surrounding the conventional financial system of most economies especially the western economies and even economies that practice dual financial system are still not left out. This study seeks to examine riba and why it should be carved out of financial transactions. The study reveals that the no religion permits the consumption of riba in whatever form and concluded that the continuous consumption of riba will impoverish the economies of the world and even the welfare of citizens will not be left out because it is a tool that does not work in increasing utility.